Hepatocellular carcinoma and the Fontan circulation: Clinical presentation and outcomes. (1st January 2021) - Possner, Mathias; Gordon-Walker, Timothy; Egbe, Alexander C.; Poterucha, Joseph T.; Warnes, Carole A.; Connolly, Heidi M.; Ginde, Salil; Clift, Paul; Kogon, Brian; Book, Wendy M.; Walker, Niki; Wagenaar, Lodewijk J.; et al.
Abstract: Background: Fontan-associated liver disease (FALD) is universal in patients with a Fontan circulation. Hepatocellular carcinoma (HCC) is one of its severe expressions, and, though rare, frequently fatal. The purpose of this study was to describe the clinical presentation, risk factors, and outcomes of HCC in patients with a Fontan circulation. Methods: A multicenter case series of Fontan patients with a diagnosis of HCC formed the basis of this study. The case series was extended by published cases and case reports. Clinical presentation, tumor characteristics, laboratory and hemodynamic findings as well as treatment types and outcomes, were described. Results: Fifty-four Fontan patients (50% female) with a diagnosis of HCC were included. Mean age at HCC diagnosis was 30 ± 9.4 years and mean duration from Fontan surgery to HCC diagnosis was 21.6 ± 7.4 years. Median HCC size at the time of diagnosis was 4 cm with a range of 1 to 22 cm. The tumor was located in the right hepatic lobe in 65% of the patients. Fifty-one percent had liver cirrhosis at the time of HCC diagnosis. Fifty percent of the patients had no symptoms related to HCC and alpha-fetoprotein was normal in 26% of the cases. Twenty-six patients (48%) died during a median follow-up duration of 10.6 (range 1–50) months. Conclusions: HCC in Fontan patients occurs at a young age with a 1-year survival rate of only 50%. Meticulous liver surveillance is crucial to detect small tumors in the early stage. Highlights: HCC is asymptomatic at the time of diagnosis in 50% of Fontan patients. 26% of Fontan patients with HCC have a normal alpha-fetoprotein. 1-year survival after HCC diagnosis in patients with a Fontan circulation is 50%. Meticulous liver surveillance is important in patients with a Fontan circulation.